Capsule endoscopy in young patients with iron deficiency anaemia and negative bidirectional gastrointestinal endoscopy. Issue 7 (1st November 2017) - Yung, Diana E; Rondonotti, Emanuele; Giannakou, Andry; Avni, Tomer; Rosa, Bruno; Toth, Ervin; Lucendo, Alfredo J; Sidhu, Reena; Beaumont, Hanneke; Ellul, Pierre; Negreanu, Lucian; Jiménez‐Garcia, Victoria Alejandra; et al.
Abstract : Background: Recent data imply young patients (age ≤50 years) undergoing small‐bowel (SB) capsule endoscopy (CE) for iron deficiency anaemia (IDA) show higher diagnostic yield (DY) for sinister pathology. We aimed to investigate DY of CE in a large cohort of young IDA patients, and evaluate factors predicting significant SB pathology. Materials and methods: This was a retrospective, multicentre study (2010–2015) in consecutive, young patients (≤50 years) from 18 centres/12 countries, with negative bidirectional gastrointestinal (GI) endoscopy undergoing SBCE for IDA. Exclusion criteria: previous/ongoing obscure‐overt GI bleeding; age <19 or >50 years; comorbidities associated with IDA. Data retrieved: SBCE indications; prior investigations; medications; SBCE findings; final diagnosis. Clinical and laboratory data were analysed by multivariate logistic regression. Results: Data on 389 young IDA patients were retrieved. In total, 169 (43.4%) were excluded due to incomplete clinical data; data from 220 (122F/98M; mean age 40.5 ± 8.6 years) patients were analysed. Some 71 patients had at least one clinically significant SBCE finding (DY: 32.3%). They were divided into two groups: neoplastic pathology (10/220; 4.5%), and non‐neoplastic but clinically significant pathology (61/220; 27.7%). The most common significant but non‐neoplastic pathologies were angioectasias (22/61) and Crohn's disease (15/61). On multivariate analysis, weight loss and lower mean corpuscular volume(MCV) were associated with significant SB pathology (OR: 3.87; 95%CI: 1.3–11.3; p  = 0.01; and OR: 0.96; 95%CI: 0.92–0.99; p  = 0.03; respectively). Our model also demonstrates association between use of antiplatelets and significant SB pathology, although due to the small number of patients, definitive conclusions cannot be drawn. Conclusion: In IDA patients ≤50 years with negative bidirectional GI endoscopy, overall DY of SBCE for clinically significant findings was 32.3%. Some 5% of our cohort was diagnosed with SB neoplasia; lower MCV or weight loss were associated with higher DY for SB pathology.